2006
DOI: 10.1093/ietele/e89-c.11.1605
|View full text |Cite
|
Sign up to set email alerts
|

Vision Chip Architecture for Detecting Line of Sight Including Saccade

Abstract: SUMMARYRapid eye motion, or so called saccade, is a very quick eye motion which always occurs regardless of our intention. Although the line of sight (LOS) with saccade tracking is expected to be used for a new type of computer-human interface, it is impossible to track it using the conventional video camera, because of its speed which is often up to 600 degrees per second. Vision Chip is an intelligent image sensor which has the photo receptor and the image processing circuitry on a single chip, which can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The authors have indicated that the positions of both the pupil and the Purkinje's image in the infrared eye image can be detected by the following five operation procedures [7].…”
Section: Image Processing For Los Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors have indicated that the positions of both the pupil and the Purkinje's image in the infrared eye image can be detected by the following five operation procedures [7].…”
Section: Image Processing For Los Detectionmentioning
confidence: 99%
“…The position detection performed by the shrink operations can eliminate these unnecessary areas prior to the detections of the pupil and the Purkinje's image eliminations by appropriate shrink operation rules [7].…”
Section: Image Processing For Los Detectionmentioning
confidence: 99%
See 3 more Smart Citations